The Effect of Peer Support of Mothers of Children with Acute Lymphoblastic Leukemia on Quality of Life of Patients - Fereshteh Ghaljaei; Sedighe Fooladi; Azam Jamali; Nasrin Mahmoodi; Bahare Zarei (Hamadan University of Medical Sciences, 2020)
Background & Aim: Caring for a child with cancer can be deeply frustrating for parents with high levels of anxiety and psychological distress. Parents who suffer from high psychological stress have poorer performance in the family and health-related quality of life in their children is significantly lower. Previous research has demonstrated the effectiveness of peer support in reducing levels of parental psychological distress. This study was aimed to investigate the effect of peer support of mothers of children with acute lymphoblastic leukemia (ALL) on quality of life of patients. Methods: This is a quasi-experimental study which was performed on 74 mothers of children with ALL hospitalized in Hematology ward of Ali ibn Abi Talib Hospital in Zahedan in 2017. Convenience sampling was used to recruit the participants in accordance with the inclusion criteria. The subjects were randomly assigned to the control and intervention groups. Peer group training was then conducted for the intervention group for five days. KID-KINDL questionnaire to parent report was completed before intervention, immediately and two months after intervention for both intervention and control groups. Data were analyzed using descriptive and inferential tests at the significant level P-value<0.05. Results:   Before intervention, the mean score of total quality of life and its dimensions were not significantly different between the two groups (P>0.05). Analysis of variance with repeated measures indicated that the mean scores of total quality of life and its dimensions in the intervention group were significantly increased over time (P<0.001). Conclusion: Using peer support program for mothers of children with ALL can improve the quality of life of children. Therefore, it is recommended to use this method alone or in combination with other methods to improve the quality of life of children with ALL.